Brexit Towards UK Sustainable Urban Development: Assessing Shifts in EU-UK Resilience Strategies - Santoso, Ashton; Mumtazah, Hilya Khalisha (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2024)
The departure of the United Kingdom from the European Union, following the Brexit referendum, has had a profound impact on UK policies and strategies across various sectors. This influence is particularly significant in the field of sustainable urban development, which previously relied on substantial EU funding sources. The cessation of significant EU funding pushed the UK to realign its sustainable development strategy. This paper explores the repercussions of Brexit on UK sustainable urban development policies, highlighting the need for new funding strategies and resilience measures. It critically analyzes how the UK is adapting to these changes and evaluates the effectiveness of its post-Brexit strategies in sustaining urban growth. This analysis is conducted within the framework of neoliberal institutionalism, which provides insights into how international organizations like the European Union and the UK government interact in the context of shifting power dynamics and national interests. Keywords: Brexit; Sustainable Urban Development; European Union; United Kingdom; Resilient Cities